2013
DOI: 10.1161/circulationaha.112.000580
|View full text |Cite
|
Sign up to set email alerts
|

Homoarginine Levels Are Regulated by l -Arginine:Glycine Amidinotransferase and Affect Stroke Outcome

Abstract: Background— Endogenous arginine homologues, including homoarginine, have been identified as novel biomarkers for cardiovascular disease and outcomes. Our studies of human cohorts and a confirmatory murine model associated the arginine homologue homoarginine and its metabolism with stroke pathology and outcome. Methods and Results— Increasing homoarginine levels were independently associated with a reduction in all-cause mortality in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
164
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(176 citation statements)
references
References 46 publications
3
164
1
5
Order By: Relevance
“…Furthermore, a possible harmful effect of elevated l-homoarginine has been proposed (Van der Zwan et al 2013), which may imply a U-shaped relationship between l-homoarginine and eGFR. Genome-wide association studies and knockout experiments identified l-arginine:glycine amidinotransferase (AGAT) as the biosynthetic enzyme for l-homoarginine (Choe et al 2013;Kleber et al 2013), and a distinct allele frequency for single-nucleotide polymorphisms was identified in black participants, correlating with higher l-homoarginine concentrations in black men and women (Atzler et al 2014). Whether these findings are of pathophysiologic relevance in cardiovascular disease deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a possible harmful effect of elevated l-homoarginine has been proposed (Van der Zwan et al 2013), which may imply a U-shaped relationship between l-homoarginine and eGFR. Genome-wide association studies and knockout experiments identified l-arginine:glycine amidinotransferase (AGAT) as the biosynthetic enzyme for l-homoarginine (Choe et al 2013;Kleber et al 2013), and a distinct allele frequency for single-nucleotide polymorphisms was identified in black participants, correlating with higher l-homoarginine concentrations in black men and women (Atzler et al 2014). Whether these findings are of pathophysiologic relevance in cardiovascular disease deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Guanidinoacetate methyltransferase (GAMT) methylates guanidinoacetate to form creatine. Creatine inhibits AGAT-catalyzed synthesis of l-homoarginine in vivo in mice (Choe et al 2013;Kayacelebi et al 2015b), presumably by reacting with the SH group of AGAT-Cys 407 disorders. ADMA is generally believed to exclusively exert its biological actions by inhibiting NOS-catalyzed synthesis of NO from Arg.…”
Section: Introductionmentioning
confidence: 99%
“…These issues include the biosynthesis and metabolism of hArg. There is strong evidence from in vitro and in vivo animal experiments (Choe et al 2013) and valuable information from very few human individuals (Davids et al 2012) that arginine:glycine amidinotransferase (AGAT; EC 2.1.4.1) is the enzyme that is mainly responsible for the synthesis of hArg. Yet, the precise mechanism of this biosynthetic route and the factors which may modulate this reaction are essentially unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in NO bioavailability and in circulating ADMA, SDMA and hArg concentrations have been intensively studied in cardiovascular diseases (CVD) in recent decades establishing high ADMA and low hArg concentrations as cardiovascular risk factors associated with cardiovascular and all-cause mortality (Böger et al 2009;März et al 2010;Pilz et al 2011;Drechsler et al 2011;Choe et al 2013;Atzler et al 2013Atzler et al , 2014Pilz et al 2014Pilz et al , 2015a. Moreover, recent studies on rheumatoid arthritis have demonstrated a positive association of inflammatory burden with ADMA levels independent of classical CVD risk factors (Sandoo et al 2014), suggesting a pivotal role of altered NO metabolism in chronic inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%